Recent Investigations of Ergot Alkaloids Incorporated into Plant and/or Animal Systems - James Levi Klotz (Frontiers Research Topics, 2015)
Ergot alkaloids produced by fungi have a basic chemical structure but different chemical moieties at substituent sites result in various forms of alkaloids that are distinguishable from one another. Since the ergoline ring structure found in ergot alkaloids is similar to that of biogenic amines (neurotransmitters), a variety of physiological effects can result after ingestion. Research involving ergot alkaloids is an increasing important global issue as more governments pass laws that limit permissible levels of ergot alkaloids in both foodstuffs and feedstuffs. Regardless of whether these compounds are found directly in foodstuffs or in feed/plants given to forage animals (i.e., cattle, horses, sheep, and goats), introduction of these compounds can complicate the food supply. In addition, toxicosis resulting from alkaloids can be a costly hindrance, with mounting annual production losses associated with forage-animal production systems that impact other agricultural and food based industries. Recent advances for the analysis of these compounds in different matrices as well as the understanding the role these compounds play in distinct biological pathways have begun to help address the issue. This Research Topic has developed a novel platform where different groups share recent data in their investigations with ergot alkaloids. The presented collection of articles emphasizes the complexity of this issue and the multiple approaches necessary to resolve the global ergot alkaloid challenges.